Coordination Behavior of 3-Ethoxycarbonyltetronic Acid towards Cu(II) and Co(II) Metal Ions - Giorgos Athanasellis; Georgia Zahariou; Stefanos Kikionis; Olga Igglessi-Markopoulou; John Markopoulos (Bioinorganic Chemistry and Applications)
Tetronic acids, 4-hydroxy-5H-furan-2-ones, constitute a class of heterocyclic compounds with potent biological and pharmacological activity. The β,β′-tricarbonyl moiety plays an integral role in biological systems and forms a variety of metal complexes. In this report, we present the complexation reactions of 3-ethoxycarbonyl tetronic acids with acetates and chlorides of Cu(II) and Co(II). These complexes have been studied by means of EPR spectroscopy and magnetic susceptibility measurements. From the obtained results, a preliminary complexation mode of the ligand is proposed.